Relationship between serum ferritin and endocrinopathies in thalassemic children: A hospital-based study - Kataki, Rita Panyang; Bharati, Sagarika (Indian Journal of Child Health, 2019)
Background: Thalassemia syndromes are a heterogeneous group of Mendelian disorders characterized by lack of/decreased synthesis of either ?/? globin chains of hemoglobin. It results in ineffective erythropoiesis and lysis of mature red blood cells in the spleen. Thalassemic patients require multiple blood transfusions which led to iron overload. Objective: This study evaluated endocrinopathies in thalassemic patients of age 5–18 years and relationship with serum ferritin level. Materials and Methods: This is a hospital-based cross-sectional study on 70 transfusion dependent thalassemic children of 5–18 years attending the department of pediatrics, of a tertiary care hospital in Assam. Their height, sexual maturity rating, serum ferritin, calcium, alkaline phosphatase, phosphate, thyroid stimulating hormone, random blood sugar, and fasting blood sugar were recorded. The data were analyzed statistically and p 0.05) in thalassemic children with normal puberty. The mean serum ferritin in stunted thalassemic children was 2909.86±820.93 ng/ml and it was 1421.43±283.41 ng/ml (p